2012
DOI: 10.1073/pnas.1209918109
|View full text |Cite
|
Sign up to set email alerts
|

Grid cell firing patterns signal environmental novelty by expansion

Abstract: The hippocampal formation plays key roles in representing an animal's location and in detecting environmental novelty to create or update those representations. However, the mechanisms behind this latter function are unclear. Here, we show that environmental novelty causes the spatial firing patterns of grid cells to expand in scale and reduce in regularity, reverting to their familiar scale as the environment becomes familiar. Simultaneously recorded place cell firing fields remapped and showed a smaller, tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
255
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(287 citation statements)
references
References 44 publications
22
255
3
1
Order By: Relevance
“…Barry et al (19) showed that manipulations to the width and length of a familiar enclosure resulted in similar transformations of the rodents' grids: When the familiar environment was elongated, the grid patterns elongated similarly. Also in rats, grids have been shown to display expansion upon introduction to a novel environment and then relax back to the original scale when the environment becomes familiar (18). Combined, these results suggest that grid cells might have a default scale but that the default scale could be influenced by experience in the given environment.…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…Barry et al (19) showed that manipulations to the width and length of a familiar enclosure resulted in similar transformations of the rodents' grids: When the familiar environment was elongated, the grid patterns elongated similarly. Also in rats, grids have been shown to display expansion upon introduction to a novel environment and then relax back to the original scale when the environment becomes familiar (18). Combined, these results suggest that grid cells might have a default scale but that the default scale could be influenced by experience in the given environment.…”
mentioning
confidence: 76%
“…The largest dataset included neurons classified as displaying significant spatially periodic activity based on spatial spectral analysis of the single units. The other two smaller datasets were both classified as "putative grid cells" (PGCs) based on their conformity of gridness scores to the definition used in studies and referred to herein as the Barry-Krupic (BK) method (11,18). The difference between the second and third datasets was that the third dataset, in addition to being defined based on the BK method, was subjected to a thorough validation against theta modulation and directional tuning.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Within modules of grid cells, cell assemblies respond with coherent changes in grid phase, grid orientation and grid scale when the animal is brought to a different environment 12,24 or following interventions that change the scale of the grid, such as exposure to an unfamiliar environment 25,78,79 or compression of the recording enclosure 24,25 . In each case, the relationship between firing fields of cell pairs is conserved despite major changes in the properties of individual cells and without any obvious relationship to sensory inputs 78 .…”
Section: Attractor Network and Mechanisms Of The Grid Patternmentioning
confidence: 99%